Al borde del naufragio : democracia, violencia y problema étnico en el Perú - Montoya, Rodrigo, 1943- (Talasa (Madrid, Spain) ;, 1992)
"Beautifully written collection of essays delineates the debate in Peru on different aspects of ethnicity: ethnic identity (what does it mean to be Peruvian? indigenous?), democracy (how can a society be democratic when a significant number of ethnic groups are denied democratic participation?), and political violence (structural violence from both the right and the left suffered by ethnic minorities)"--Handbook of Latin American Studies, v. 57.